Analisis Program Aplikasi Sistem Informasi Aktivitas Santri dalam Meningkatkan Kedisiplinan Santriwati di Pondok Modern Daarul Hikmah Bontang Tahun Pelajaran 2023/2024 - Putri, Syahfiranti; Ihsan, Muh. (NABAWI: Jurnal Penelitian Pendidikan Islam, 2025)
This research aims to analyze the Information System Application for Student Activities (SIAS) program in improving the discipline of female students at Pondok Modern Daarul Hikmah Bontang during the 2023/2024 academic year. This study employs a qualitative descriptive approach, with data collection methods including observation, interviews, and documentation. The results of the study indicate that the use of the SIAS application has a positive impact on the discipline of female students. The application assists the Musyrifah in effectively supervising and controlling the activities of female students within the Pondok Modern Daarul Hikmah Bontang environment through Android phones. Additionally, the presence of the SIAS application has led to increased discipline among female students, as evidenced by their participation in boarding school activities and a reduction in rule violations. The implications of the Information System Application for Student Activities are designed by considering needs that encompass various important aspects, as the application is equipped with features that greatly aid in the supervision and control of female students' activities.